The reign of Alexander II, 1214-49 - Oram, Richard D. (Northern world ;, 2005)
This nine-essay volume provides the first full-length, detailed exploration of the kingdom of Scotland during the reign of Alexander II (1214-49), and the most extensive analysis of this key state-builder and his policies.